Efficacy of Per Rectal Non-Steroidal Anti-inflammatory Drugs to Prevent Post Endoscopic Retrograde Cholangiopancrea-tography Pancreatitis: A Comparative Study (Bangladesh Journal of Medicine, 2021)
Background and aims: Acute pancreatitis is the most common major post-ERCP complication ranging as high as 10% to 40%. Rectal NSAIDS (Indomethacin or Diclofenac) seem to be the most promising drugs to prevent post ERCP pancreatitis. We performed a trial to investigate the efficacy of indomethacin or diclofenac.Methods: A prospective randomized comparative trial was performed at Dhaka from January 2013 to June 2019. Patients undergoing ERCP were randomly selected to group-A and group-B. Diclofenac 50mg suppository was given to group-A patients and Indomethacin 100mg suppository was given to group-B patients during or just after ERCP. The primary outcome was acute pancreatitis following the procedure which was defined by new upper abdominal pain, elevation of pancreatic lipase to at least 3 times the upper limit of normal level 24 hours after ERCP and hospitalization for 02 nights. Retrospective analysis of data of 122 patients who had undergone ERCP in 2012 but had no history of rectal NSAIDS (group C) was done.Results: Total 613 patients were included in this study and followed up. Post ERCP pancreatitis developed in 21(8.5%) patients of group-A (n=247), in 19(7.78%) patients of group-B (n=244) and in 20(17.85%) patients of group-C (n=122)(p=0.02). Moderate to severe pancreatitis was found in 08(3.23%) patients of group-A, in 06(2.45%) patients of group-B and in 12(9.83%) patients of group-C(p= 0.01). Administration of these NSAIDS showed clear benefit to reduce occurrence of Post ERCP pancreatitis when compared with no drug group (P=0.01). The efficacy of indomethacin compared with diclofenac was similar (P=0.874).Conclusions: Prophylactic use of rectal indomethacin or diclofenac during or just after ERCP significantly reduces the incidence of post ERCP pancreatitis. These NSAIDs are inexpensive, safe and should be used routinely in each patient undergoing ERCP.Bangladesh J Medicine July 2021; 32(2) : 99-106